Body Temperature and Activity Rhythms Under Different Photoperiods in High Arctic Svalbard ptarmigan (Lagopus muta hyperborea) - Appenroth, Daniel; Nord, Andreas; Hazlerigg, David G.; Wagner, Gabriela C. (Frontiers in Physiology, 2021)
Organisms use circadian rhythms to anticipate and exploit daily environmental oscillations. While 14 circadian rhythms are of clear importance for inhabitants of tropic and temperate latitudes, its role for 15 permanent residents in the polar regions (where there are constant photic conditions for a large part of 16 the year) is less well understood. The high Arctic Svalbard ptarmigan shows behavioural rhythmicity 17 in presence of light-dark cycles but is arrhythmic in constant photic conditions (i.e., during the polar 18 day and polar night). This has been suggested to be an adaptation to the unique light-dark cycles in the 19 Arctic. In this study, we examined regulatory aspects of the circadian control system in the Svalbard 20 ptarmigan by recording core body temperature (Tb) alongside locomotor activity in captive birds under 21 different photoperiods. We show that Tb and activity are rhythmic with a 24-h period under short (L:D 22 6:18) and long photoperiod (L:D 16:8). Under constant light and constant darkness, Tb is arrhythmic 23 and activity shows signs of ultradian rhythmicity. Birds under short photoperiod also showed a rise in 24 Tb preceding dawn and any rise in activity, which proves that the light-on signal can be anticipated, 25 most likely by a circadian system.